Rifampicin Enhanced Carbapenem Activity with Improved Antibacterial Effects and Eradicates Established Acinetobacter baumannii Biofilms - Lois Chinwe Nwabor; Arnon Chukamnerd; Ozioma Forstinus Nwabor; Rattanaruji Pomwised; Supayang P. Voravuthikunchai; Sarunyou Chusri (MDPI AG, 2023)
Biofilm-mediated infections are critical to public health and a leading cause of resistance among pathogens, amounting to a prolonged hospital stay and increased mortality rate in the intensive care unit. In this study, the antibacterial and antibiofilm activities of rifampicin or carbapenem monotherapies were compared with rifampicin and carbapenem combination therapies against rifampicin-resistant and carbapenem-resistant Acinetobacter baumannii isolates. Among 29 CRAB isolates, 24/29 (83%) were resistant to rifampicin, with MIC values between 2-256 µg/mL. Checkerboard assays disclosed that combination therapies at FICIs between 1/8 and 1/4 improved the activity of carbapenems at subinhibitory concentrations. Time-kill kinetics indicated a 2- to 4-log reduction at 1/2 MIC rifampicin + 1/4 MIC carbapenem and 1/4 MIC rifampicin + 1/4 MIC carbapenem against the isolates, with the MIC values ranging from 2-8 µg/mL. The MTT assay revealed a dose-dependent decrease of the cell viability of established bacterial biofilm at 4 MIC rifampicin + 2 MIC carbapenems, with a percentage reduction of 44-75%, compared with monotherapies at 16 MIC. Scanning electron microscopy further confirmed bacterial cell membrane disruption, suggesting a synergism between carbapenem and rifampicin against a representative isolate. The findings demonstrated that the combination of rifampicin with carbapenems could improve antibacterial activities and eradicate established Acinetobacter baumannii biofilm.